Validation of GLIM malnutrition criteria for diagnosis of malnutrition in ICU patients: An observational study. Issue 5 (May 2021) - Theilla, Miriam; Rattanachaiwong, Sornwichate; Kagan, Ilya; Rigler, Merav; Bendavid, Itai; Singer, Pierre
Summary: Background & aims: Patients in the Intensive Care Unit (ICU) are at high risk of malnutrition. The only validated malnutrition assessment tool is the Subjective Global Assessment (SGA). The Global Leadership Initiative on Malnutrition (GLIM) is a new malnutrition assessment tool. The present study compares the nutrition-related parameters of the following tools: GLIM tool, SGA, Phase Angle (PA), Low Fat-Free Mass Index (FFMI), and Patient- and Nutrition-Derived Outcome Risk Assessment score (PANDORA), in an attempt to validate an objective tool. Methods: Eighty-four ICU patients were included. The tools mentioned above were assessed for their validity in diagnosing malnutrition. All patients were defined as suffering from acute disease and received medical nutrition therapy. To evaluate whether there is a correlation between the GLIM criteria, SGA, PA, and low FFMI, we compared the SGA, PA, and low FFMI to the GLIM criteria using Spearman correlation coefficients and a Chi-square test. Also, a Mann–Whitney U test was used to test the mean differences between the GLIM criteria and the PANDORA. The area under the curve (AUC) of the proposed parameters was evaluated for diagnosis of malnutrition to seek cutoff points that yield good sensitivity and specificity. Results: Mean age was 50 ± 20 years, BMI 25.3 ± 5.1 kg/m 2, APACHE II 20.5 ± 7.7, PANDORA score 32 ± 8.5. GLIM malnutrition criteria were significantly correlated with the gold standard SGA assessment and with low FFMI, with PA (Phase Angle), and with the PANDORA score. The area under the curve, by using the ROC curve analysis for GLIM criteria stratified by the SGA results, was 0.85 (P < 0.001). Sensitivity was 85%, and specificity 79%. However, when comparing the low FFMI, PA, and PANDORA to the GLIM criteria, the ROC curve analysis results were considered poor rank. Conclusions: The SGA malnutrition assessment highly validated the GLIM criteria framework combined with the two-criteria diagnosis of malnutrition with a high level of precision. The GLIM malnutrition assessment seems to be acceptable in the ICU setting.